On the influence of gamma prime upon machining of advanced nickel based superalloy - Liao, Zhirong; Axinte, Dragos; Mieszala, Maxime; M’Saoubi, Rachid; Abelhafeez, Ali; Michler, Johann; Hardy, Mark (Elsevier, 2018)
Whilst gamma prime (γ’) phase is the strengthening phase in Ni-based superalloys its influence on machining has been seldom investigated. This paper reports for the first time on the effect of γ’ upon machining of Ni-based superalloys when cutting with parameters yielding different cutting temperature intervals which lead to strengthening/softening effects on the workpiece (sub)surface. In-depth XRD, SEM/FIB, EBSD analysis and unique micro-pillar testing in the workpiece superficial layers indicated that with the increase of γ’ fraction the grain plastic deformation significantly decreased, while specific cutting energy can switch from low to high values influenced by the real cutting temperature.